The Unreal game engine ; a comprehensive guide to creating playable levels - Finch, Andrew, (Animator), ....- (S.l. : 3DTotal Publishing, 2013)
The Unreal game engine is a versatile system that has been used to power a variety of best-selling video games. In The Unreal Game Engine, environment artist Andrew Finch looks at how to create game levels using the free Unreal Development Kit, from modeling the environment and building objects to adding those objects to the scene, texturing, and lighting. If you've ever wondered what it would be like to be a level designer, then look no further!
Includes index.
Keywords: Computer games -- Design; Unreal Development Kit